Significance of Proficient Communication on Career Choice Among First Years in Rural South Africa (Journal of Student Affairs in Africa, 2021)
Career choice involves the selection of one occupation over another. It is very important as it gives people focus on what career to follow. However, a lack of adequate information on career choice is capable of negatively influencing career choices. Hence, this study examines the significance of the adequate information on career choice among first year students using a selected rural South African university. A quantitative research method was employed for data collection. Purposive and random sampling was used to select the institution and sample respectively. Questionnaires were administered to 375 randomly selected first year students studying in the selected rural South African university. The findings of the study show that career choice is important and can contribute to the success of students. Attempts are made to communicate about career pathways with students while in high schools through the provision in the curriculum. Various factors ranging from parental influence, teachers, presence or absence of career counsellors, amongst others affect the career choice of students. The study recommends that education stakeholders, inclusive of parents, should be informed on the need to guide students in making informed career choices. Career information centres should be made available to students in various locations in the country.
Keywords: career choice; career guidance; first year students; proficient communication; rural South Africa